Βιβλιοκρισία:D. MARJANOVIC, Creating Memories in Late 8th-century Byzantium. The Short History of Nikephoros of Constantinople [Central European Medieval Studies], Amsterdam University Press 2018 - ΚΙΑΠΙΔΟΥ Ειρήνη-Σοφία (Byzantina Symmeikta, 2019)
Βιβλιοκρισία:D. Marjanović, Creating Memories in Late 8th-century Byzantium. The Short History of Nikephoros of Constantinople [Central European Medieval Studies], Amsterdam University Press 2018